Corrigendum to ‘Photophysical properties and photoelectrochemical performances of sol-gel derived copper stannate (CuSnO3) amorphous semiconductor for solar water splitting application’ [Ceramics International (2018) 1843–1849](S027288421732312X)(10.1016/j.ceramint.2017.10.119) - Kim, Bit Na; Seo, Gab Kyung; Hwang, Sung Won; Yu, Hakki; Ahn, Byungmin; Seo, Hyungtak; Cho, In Sun (Ceramics International, 2018)
The authors regret that the incorrect version of Fig. 4 appeared in this article. The correct version of this figure is reproduced below. The authors would like to apologise for any inconvenience caused.